Development of Food-Based Recommendation and Nutrient-Dense Meal for Female Shift Workers in West Java, Indonesia - Puji Lestari, Shanti; Adi, Nuri Purwito; Fahmida, Umi; Kusuma Dewi, Dian; Mansyur, Muchtaruddin (UI Scholars Hub, 2023)
Introduction. Some manufacturing industries employ not only male workers but also female workers, who are required to undergo shift work. Given the altered eating habits as well as metabolic and endocrine profiles of shift workers, this will affect their nutritional needs. Considering that anemia that occurs in female workers is primarily nutritional anemia, this becomes a challenge in the field of occupational nutrition, especially in terms of preparing food for female workers in accordance with their nutritional needs. The aim of the study is to develop a set of FBR for female shift workers using the Linear Programming (LP) approach. Methods. Dietary data were collected in a cross-sectional survey of female shift workers (n=106) working at a textile factory in Sumedang District, West Java, Indonesia, and a market survey in two local markets. Optifood software was used for LP analysis particularly to identify problem nutrients, and nutrient-dense foods, and compare alternative FBRs. The nutrient-dense menu was developed using the identified nutrient-dense foods. Results. The problem nutrients were iron (absolute) and calcium (partial), and the remaining nutrients were still dietary inadequate. The nutrient-dense menu including iron-rich and folate-rich foods can fulfill the nutrient gap for iron from the final FBR (15% RNI of the 7% RNI). Conclusion. The inclusion of a nutrient-dense menu for the female factory workers helped to meet the nutrient gap for iron which is the absolute problem nutrient in the optimized FBR. The promotion of optimized FBR and the provision of a nutrient-dense menu should be part of the occupational nutrition program.